Punctate Palmoplantar Keratoderma - Susana Cláudia Teixeira; André Coelho Almeida; Joana Carvalho; Paulo Morais (Gazeta Médica, 2021)
A 5-year-old caucasian boy, born of non-consanguineous parents, was referred to the dermatology department due to palmar hiperlinearity and multiple 2-3 mm hyperkeratotic circular lesions in the soles (Fig. 1). The remaining physical examination was unremarkable. There was a family history of palmoplantar hyperkeratosis in the mother and maternal grandfather. To spare the child, a punch skin biopsy was taken from his mother. Pathology revealed an epidermis with irregular acanthosis and orthokeratotic hyperkeratosis, without other morphologic alterations (Fig. 2). Clinical aspect of the lesions associated with a positive family history and histologic findings allowed the diagnosis of punctate palmoplantar keratoderma. Satisfactory results were achieved with urea 20% cream and emollient applied to the soles. [...]